Schools for conflict or for peace in Afghanistan - Burde, Dana (Columbia University Press, 2018)
Foreign-backed funding for education does not always stabilize a country and enhance its statebuilding efforts. Dana Burde shows how aid to education in Afghanistan bolstered conflict both deliberately in the 1980s through violence-infused, anti-Soviet curricula and inadvertently in the 2000s through misguided stabilization programs. She also reveals how dominant humanitarian models that determine what counts as appropriate aid have limited attention and resources toward education, in some cases fueling programs that undermine their goals.